2020
DOI: 10.1186/s13031-020-00302-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a video library tool to support community health worker counseling in rural Afghan districts: a cross-sectional assessment

Abstract: Background: Rural Afghan populations have low skilled birth attendance rates and high maternal and infant mortality. Insecurity and armed conflict, geographic barriers, and cultural norms often hinder women's access to facility-based reproductive, maternal, newborn, and child health (RMNCH) services. Community health workers (CHWs) are critical agents for behavioral change in this and similarly fragile settings, where RMNCH information exposure is limited by low literacy and mass media access. We assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Other interventions identified in our review included advanced distribution of misoprostol ( Smith et al. , 2014a ; 2014b ); the use of health video libraries for community counselling ( Dal Santo et al. , 2020 ); a combined programme of modern contraceptive use, antenatal care and skilled birthing attendance ( Viswanathan et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other interventions identified in our review included advanced distribution of misoprostol ( Smith et al. , 2014a ; 2014b ); the use of health video libraries for community counselling ( Dal Santo et al. , 2020 ); a combined programme of modern contraceptive use, antenatal care and skilled birthing attendance ( Viswanathan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Material resources included integrating technology in the care process [e.g. computer tablet-based health video library ( Dal Santo et al. , 2020 )] and offering free care [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Health providers should consider using visual or audio rather than written material to improve communication and health literacy. A study in Afghanistan found a high satisfaction rate with community health workers who used a computer tablet-based health video library to enhance health counseling sessions [27].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of CHWs and mobile technology concluded that despite relatively low levels of education and minimal training among a community volunteer cadre, the use of video and other job aids could help to improve their performance in the provision of care [ 5 ]. In addition, the importance of using video demonstration to facilitate learning of new behaviors has been documented [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that engaging caregivers to discuss how they would undertake nurturing care activities provided an opportunity for self-reflection, problem solving, and the identification of individualized actions. A study on how CHWs used ECD videos in India found the PLOS GLOBAL PUBLIC HEALTH tools helped them to better engage and educate clients [19]. Another study in India showed improved CHW performance through use of videos to engage women in dialogue to practice healthy behaviors [12].…”
Section: Discussionmentioning
confidence: 99%